Pseudo-Gaucher cells. Issue 4 (April 1992) - Carrington, P A; Stevens, R F; Lendon, M
Abstract : A case of acute lymphoblastic leukaemia, associated with cells resembling Gaucher cells in the bone marrow, is reported. The patient had no evidence of inherited Gaucher's disease and the ultrastructural appearance of the cells was consistent with pseudo-Gaucher cells described in other haematological diseases. This is the first report of these cells in association with acute lymphoblastic leukaemia.